Sociodemographic factors related to the proper use of masks and appropriate social distancing to prevent the spread of SARS-CoV-2 in a food market in Lima, Peru - Hurtado-Cuba, Renzo (2021)
Objective: To determine the relationship that sociodemographic factors have with the proper use of masks and appropriate social distancing to prevent the spread of SARS-CoV-2 in people who attend the Surquillo No. 2 market (Lima, Peru). Materials and methods: A quantitative, observational, descriptive, cross-sectional and prospective community study. Both a survey and a checklist were administered to 385 subjects who attended the Surquillo market between Septemberand October 2020. The sample size was obtained using Epidat 4.2 with an expected proportion of inadequate practices of 50 %, a confidence level of 95 % and an absolute precision of 5 %. Non-probability convenience sampling was used. The information was analyzed using IBM SPSS Statistics V25. Descriptive and analytical statistics were performed using the chi-square test and logistic regression with a confidence level of 95 % and p < 0.05. Results: Forty-eight point eight zero percent (48.80 %) of the research participants were males. Their mean age was 42.61 ± 13.84 years. Sixty-four point seven zero percent (64.70 %) (n = 249) had higher (technical and university) education, 47.50 % (n = 183) lived in Surquillo, 42.90 % (n = 165) were self-employed, 48.80 % (n = 188) wore a well-fitting mask in good condition, 32.20 % (n = 124) covered their nose and mouth properly, 35.10 % (n = 135) used cotton masks, 70.00 % thought that a distance of 1.5 m should be kept from others, and 94 % maintained a physical distance of less than 1.5 m during the observation. There was a significant relationship between the higher education level and the proper use of masks (p < 0.001) but not between the education level and social distancing. Conclusions: There is a significant relationship between the education level and the proper use of masks.